Kinetic study of solid-liquid extraction of caffeine in Ilex guayusa Loes - Luna-Fox, Sting; Uvidia-Armijo, Jhoeel; Rivera-Barreto, Jannys (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The kinetic study of the solid-liquid extraction of caffeine in Ilex guayusa Loes addresses a critical stage in the isolation of alkaloids such as caffeine. Solid-liquid extraction, a widely used technique, plays a fundamental role in obtaining these compounds. The study aimed to evaluate the applicability of the Peleg equation to model the solid-liquid extraction of caffeine in Ilex guayusa Loes leaves. Caffeine content was determined by UV-visible absorption spectroscopy. Extraction kinetics were estimated using the two-parameter Peleg’s equation. The correspondence between the experimental results and those predicted by the model was established by calculating Pearson's correlation. The results indicated significant extraction temperature and time effects on caffeine content, with concentrations ranging from 0.24 to 1.52 g.100 g-1 at different extraction temperatures (30, 40, and 50 °C). The Peleg equation effectively modeled caffeine extraction kinetics, with high Pearson correlation coefficients (0.96895 to 0.99685) confirming its suitability for predicting caffeine concentration. These results highlight the importance of understanding extraction kinetics to optimize caffeine extraction processes, offering valuable insights for industries using Ilex guayusa Loes extracts.